Interoperability Blockchain, InterPlanetary File System and Health Level 7 Framework for Electronic Health Records - Bran, Estefano; Alzamora, Adrian; Castañeda-Carbajal, Bruno; Castillo-Sequera, José Luis; Wong, Lenis (International Journal of Online and Biomedical Engineering (iJOE), 2024)
Patient medical records and their accurate recording, storage, protection, and access are essential elements to high-quality healthcare. While many parts of the world have moved to traditional digital systems and electronic health records (EHRs), these systems require complex evaluation and large infrastructure investments, lack interoperability, and introduce the constantly-increasing challenges of cyber-attacks and digital security. The aim of this study is to address these challenges through a secure and accessible EHR management system, applied to allergy and family records, based on blockchain technology, the InterPlanetary File System (IPFS) protocol, and the health level 7 (HL7) fast healthcare interoperability resources standard. The proposal was carried out in four phases: (1) blockchain architecture design, (2) blockchain network design, (3) interoperability design, and (4) web application design. A performance evaluation of the system was conducted to determine the throughput and latency metrics. The results presented a maximum medical record reading and writing throughput of approximately eight transactions per second, with a write latency averaging 5,926 ms to 51,836 ms and a reading latency of 4,783 ms to 45,500 ms. With the addition of a survey of 21 patients and 10 healthcare professionals indicating that both groups strongly agree that the system meets the criteria of high-quality healthcare, all study results present a framework that could serve as a model for the adoption of standards-based, accessible, and secure EHR systems.